All-day continuous electrical power generator by solar heating and radiative cooling from the sky. (15th September 2022) - Yu, Li; Xi, Zhiyuan; Li, Shuang; Pang, Dan; Yan, Hongjie; Chen, Meijie
Highlights: TE generator with selective absorbers is designed for all-day electricity generation. A theoretical model is proposed to investigate the all-day electricity generation. Output power can be 4 mW m −2 (nighttime) and 489 mW m −2 (daytime) in the lab. Thermodynamic limit can be 65 mW m −2 (nighttime) and 145 W m −2 (daytime). Abstract: Thermoelectrical power generator (TEG) proves a promising way that utilizes ambient energy. However, all-day continuous power generation without an artificial heat source by the TEG remains a challenge. In this work, TEG is integrated with a selective solar absorber (SSA) to absorb heat from the heat source (i.e., the sun) and a passive daytime radiative cooling (PDRC) coating to release the heat towards the cold source (i.e., the outer space), providing all-day electrical power generation continuously. A theoretical model is proposed to investigate the all-day performance and design the device parameters (such as load ratio, area ratio, solar intensity, and convective heat transfer rate). It is found that the output power density peaks when the load ratio γ = 1.1 at the area ratio α = 1. Indoor experiments show that the output power in the nighttime and daytime can be 4 mW m −2 and 489 mW m −2 respectively while the outdoor results drop to 0.8 mW m −2 and 91 mW m −2 respectively without any thermal management. In addition, the thermodynamic limit in the nighttime and daytime can be 65 mW m −2 and 145 W m −2 respectively by replacing the TEG with a Carnot engine. These results provide a novel approach to unitizing the solar heating and out space cooling through the selective absorber/emitter, generating 24-h continuous electrical power for unsupervised small devices and remote areas.